PENERAPAN MEDIA PEMBELAJARAN PAPAN JURANG MATERI PENJUMLAHAN DAN PENGURANGAN PADA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS II SDN MAYANGAN 4 - Nur Nadifa, Rita; Prastiwi Sriwijayanti, Ribut; Hattarina, Shofia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on research conducted at SDN Mayangan 4, several problems occurred in the learning process. Second-grade students experienced difficulty in calculating addition and subtraction using fingers. Students still counted using their fingers. Some students had not yet achieved the minimum completeness criteria (KKM) of 75. In this study, the researcher examined (1) how the use of the cliff board learning media in addition and subtraction was applied to second-grade students at SDN Mayangan 4, and (2) whether there was an improvement in second-grade students' learning outcomes after the use of the cliff board learning media. This study aimed to: (1) determine how the use of the cliff board learning media in addition and subtraction was applied, and (2) determine whether there was an improvement in student learning outcomes after the use of the cliff board learning media. This study used the Classroom Action Research (CAR) method, implemented in two cycles, each cycle encompassing planning, implementation, observation, and reflection. The research subjects were 10 second-grade students, 4 boys and 6 girls. Data collection techniques included observation, testing, and documentation. The results of this study showed an increase between cycles I and II. In cycle I, the percentage of results obtained using the gap board media was 60%, with 6 out of 10 students completing it with an average score of 72. This increased to 90% in cycle II, with 9 out of 10 students completing it with a score of 80. Therefore, it can be concluded that the use of the gap board media for addition and subtraction can improve student learning outcomes and make learning more interesting and enjoyable.